Altered fecal microbiome and metabolome profiles in rat models of short bowel syndrome - Huang, Yuhua; Jiao, Jian; Yao, Danhua; Guo, Feilong; Li, Yousheng (Frontiers in Microbiology, 2023)
Short bowel syndrome (SBS) is featured by impaired nutrients and fluids absorption due to massive small intestine resection. Gut dysbiosis has been implicated in SBS, this study aimed to characterize the metagenomic and metabolomic profiles of SBS and identify potential therapeutic targets. Fecal samples from SBS and Sham rats (n = 8 per group) were collected for high-throughput metagenomic sequencing. Fecal metabolomics was measured by untargeted liquid chromatography-mass spectrometry. Our results showed that the species-level α-diversity significantly decreased in SBS rats, accompanied by altered microbiome compositions. The beneficial anaerobes from Firmicutes and Bacteroidetes were depleted while microorganisms from Lactobacillus, Escherichia, Enterococcus and Streptococcus were enriched in faces from SBS rats. LEfSe analysis identified 17 microbial species and 38 KEGG modules that were remarkably distinct between SBS and Sham rats. In total, 1577 metabolites with known chemical identity were detected from all samples, among them, 276 metabolites were down-regulated and 224 metabolites were up-regulated in SBS group. The typical signatures of SBS fecal metabolome comprised reduced short-chain fatty acids and products of amino acid metabolism (indole derivatives and p-cresol), as well as altered bile acid spectrum. We revealed 215 robust associations between representative differentially abundant microbial species and metabolites, the species with the same changing trend tended to have a similar correlation with some certain metabolites. Conclusively, the fecal microbiome and metabolome significantly altered in SBS. Our findings may lay the foundation for developing new strategies to facilitate intestinal adaptation in SBS patients.